The Effect of William Flexion Exercise on Pain Levels in Batik Crafters with Low Back Pain in Laweyan - Asmi Andin Zahira; Irma Mustika Sari (Jurnal Keperawatan Duta Medika, 2026)
Introduction:   Low Back Pain (LBP) or better known as lower back pain is felt in  lower back area, often felt between  corners of  lowest ribs to  sacrum. World Health Organization (WHO) states that around one in 13 people worldwide experience lower back pain, which is equivalent to around 619 million people worldwide. William Flexion Exercise is physical exercise system that aims to treat lower back pain without surgery. Objectives:  Determine the effect of William flexion exercise training on the level of Low Back Pain in batik craftsmen. Methods:  Pre-Experimental research type with One-Group Pre Test-Post Test Design. Sampling technique uses non-probability sampling, namely purposive sampling method. Samples were carried out on 15 batik craftsmen. William Flexion Exercise  done 6 times for 2 weeks. The analysis used was Wilcoxon sign rank test. Results:   before William Flexion Exercise intervention was carried out, highest percentage was moderate pain, 73.3%, after intervention,  highest percentage was mild pain, 80%.  Wilcoxon test obtained  p-value of 0.002<0.05, which means that there is influence of William Flexion Exercise on reducing Low Back Pain. Conclusions:  William Flexion Exercise has an effect on reducing  level of Low Back Pain in batik craftsme